Endothelins and inflammation: The gastrointestinal system - (:unkn) unknown (My University, 1999)
Endothelin (ET) is a very potent vasoconstrictor peptide produced by the vascular endothelium. Several studies have shown that the endothelin system is activated in various inflammatory conditions, including ischemia-reperfusion injury, septic shock, severe traumatic injury, colitis, stress ulcer and peptic ulcer. This article focuses on the role of ET in gastrointestinal inflammation. Particular emphasis is devoted to the contribution of ET to the modulation of gastrointestinal microcirculation and microvascular permeability and leukocyte activation and accumulation. These issues are also addressed in an integrated fashion for the pathologic condition, ischemia-reperfusion (I/R). Copyright (C) 1999 Elsevier Science Ireland Ltd.
Keywords: Endothelin; Ischemia-reperfusion; Microcirculation; Mucosal damage; PMNs; Vascular permeability